Soil physicochemical and microbiological indicators of short, medium and long term post-fire recovery in semi-arid ecosystems. (April 2016) - Muñoz-Rojas, Miriam; Erickson, Todd E.; Martini, Dylan; Dixon, Kingsley W.; Merritt, David J.
Highlights: We assessed short, medium, and long term changes in soil indicators after wildfire. Soil pH, electrical conductivity and available P are higher immediately after fire. Fungi to bacteria ratio and microbial quotient are sensitive indices of soil recovery. Changes in the microbial composition are apparent one year after the fire. Soil ecosystems partially recover in the medium term (five years following fire). Abstract: Natural disturbances such as wildfires cause significant alterations to the structure and functioning of semi-arid ecosystems. After such disturbances, the recovery of the soil ecosystem as a whole, and more specifically the belowground microbial communities, is poorly understood. In this study, we aimed to (a) assess the short, medium and long term changes in soil physicochemical and microbiological indicators and indices after a wildfire in a semi-arid environment, (b) analyse the key relationships of multiple soil parameters and indices, and (c) identify the most suitable indicators of post-fire recovery. The study was conducted across a wildfire chronosequence spanning sites recently burnt (three months) through to 14 years after fire in a semi-arid hummock grassland ecosystem of northern Western Australia. Immediate effects of the fire on the soil system were evident with increases in pH, electrical conductivity, and available nutrients. These chemical indicators showed a strong correlation with fire age and were consistent in the direction of change. Variations in the microbial composition were apparent one year after the fire, with a higher proportional abundance of bacterial communities. The fungi to bacteria ratio and the microbial quotient (proportion of microbial C to total organic C) proved to be significant indices to reflect the recovery of soils in these semi-arid environments. Overall, this study highlights the importance of understanding the post-fire response of belowground ecosystems, and particularly changes and recovery of soil microbial communities, at different time periods. The approach and methods followed in this research can be effectively extrapolated to other areas. This study can be used to inform better soil management of degraded systems in a rapidly changing climate.